Metabolic module and endothelial function in iron-deficiency anemias - V. G. Zhelobov; A. V. Tuev; L. A. Nekrutenko; A. V. Agafonov (Российский кардиологический журнал)
Hemic hypoxia influence on lipid profile and vasodilating endothelial function in iron-deficiency anemias was studied in 35 patients. Blood lipid profile, lipid peroxidation, blood antioxidant potential, and vasodilating endothelial function were assessed. Anemia, regardless of its etiology, was characterized by antiatherogenic lipid profile dynamics, antioxidant stress, and endothelial dysfunction development, that could be regarded as severe vascular dysfunction predictor. Anemic syndrome severity plays an important role in the development of metabolic dysbalance and endothelial dysfunction.